Android-Based Interactive Video Learning Media for Hijaiyah Letters for Early Childhood Education Children - Sifiyana, Selfi; Rudiyanto, Arif Rifan; Mustagfirin, Mustagfirin; Arifiani, Rina (Jurnal Ilmiah Sistem Informasi, 2025)
Learning Hijaiyah letters is an essential foundation for studying the Qur’an, especially in early childhood. Traditional learning methods are often considered less engaging because they tend to be monotonous and non-interactive. This study aims to design and develop an Android-based Hijaiyah letter learning application using the Kodular platform by implementing the Multimedia Development Life Cycle (MDLC) method. The MDLC stages include concept, design, material collection, construction, testing, and distribution. This application has several prominent features, including an introduction to Hijaiyah letters, illustrated practice questions with a randomisation system, and automatic assessment displaying learning scores. Test results show that the application runs well on various Android devices and all functions, such as navigation between screens, question randomisation, and score display, work as expected. Based on user trials, this application is practical at increasing students’ interest and understanding of Hijaiyah letters through interactive, enjoyable learning.